2016
DOI: 10.1177/0265659016630034
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood educators’ understanding of early communication: Application to their work with young children

Abstract: Young children need rich learning experiences to maximize their potential. Early childhood educators (ECEs) working in childcare have knowledge of individual children as well as skills and professional knowledge that afford opportunities to provide language-rich environments for learning. To successfully work in partnership with ECEs, speech-language pathologists need to understand what they know about early communication development and how they apply it in their work. This study explored ECEs' understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
(60 reference statements)
2
3
0
Order By: Relevance
“…The KCP was consistently on site with collaborative relationships with colleagues already in place. This supports Brebner et al (2016) in the value of consistent collaborative relationship between the trainer and trainees.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The KCP was consistently on site with collaborative relationships with colleagues already in place. This supports Brebner et al (2016) in the value of consistent collaborative relationship between the trainer and trainees.…”
Section: Discussionsupporting
confidence: 61%
“…There was a statistically significant increase in the use of one communication facilitating strategy and a decrease in their use of one conversation-hindering behaviour. Brebner et al (2016) developed a professional development programme for early years practitioners across four childcare settings where the programme was delivered for two days a week over a period of eight weeks. The programme was individualized to the practitioners and the settings in terms of learning goals and support across knowledge of and practice in supporting all children in their language development.…”
Section: Introductionmentioning
confidence: 99%
“…The data suggest that our participants attach strong significance to their role in children's language development but lack confidence and do not consider that they have adequate knowledge about developmental language milestones to identify children with or at risk for language difficulties. Our findings support previous evidence (Brebner et al., 2017 , 2016 ; Mroz, 2006a ; Scarinci et al., 2015 ) that ECTs would like further training in identifying children whose language skills may not be developing as expected. An important finding in the current study was the apparent reticence of ECTs to raise apprehensions about a child's language ability with a parent.…”
Section: Discussionsupporting
confidence: 91%
“…International studies have also revealed limited content about children's language development in preservice training courses that provide ECTs with their initial preparation that qualifies them to work as an ECT (Letts & Hall, 2003;Mroz, 2006a,b). Consistent with this, research has demonstrated that ECTs desire more training about language development (Letts & Hall, 2003;Mroz, 2006b), atypical language development and specifically, how best to support and identify children with language and other communication difficulties (Brebner et al, 2016(Brebner et al, , 2017Mroz, 2006a;Scarinci et al, 2015). These perceived knowledge gaps have been reported to affect ECTs' confidence in their knowledge about children's language development (Letts & Hall, 2003;Mroz, 2006a,b).…”
Section: Early Childhood Teachers' Knowledge and Trainingmentioning
confidence: 91%
“…For example, a VUI's dialogic interactions are pre-defined, and the efficacy of a user's interaction with the VUI is reliant on the child answering in a manner that is predictable by the VUIs designers. Thus, when a child responds in an unexpected way, the VUI cannot reliably provide comprehensible feedback [8].…”
Section: Introductionmentioning
confidence: 99%